World religions demystified - Moosa, Ebrahim E.I; Cleary, Matt (McGraw-Hill Education, 2014)
World Religions DeMYSTiFieD gives you a tour of belief systems found around the globe. You will learn about the world's major religions--Hinduism, Christianity, Judaism, Buddhism, Taoism, Confucianism, and Islam--as well as Earth-based religions and native traditions of Australia, Africa, and the Americas. After reading this book, you will have a healthy understanding of these faiths without being overwhelmed by mystifying jargon or concepts.--COVER.